Pediatric liver tumors - Zimmermann, Arthur; Perilongo, Giorgio; SpringerLink (Online service). (New York Springer, 2011)
The field of liver tumors in children has seen tremendous therapeutic advances over recent years. This has been achieved through a much better understanding of the biology of disease, improved diagnostic procedures, refined methods of pretreatment tumor staging, the implementation of highly efficient chemotherapy and surgery, detailed monitoring of toxicity, and careful follow-up strategies. International controlled trials have played a key role in these advances, and many leading figures in the trials are among the editors and authors of this book. Their principal goal in Hepatic Tumors in Ch.
Historical Background -- Epidemiology of Pediatric Liver Tumors -- Molecular Aspects of Hepatoblastoma -- Ontogenetic Aspects of Liver Tumors -- Translational Investigations of Liver Tumors: Sampling Strategies and Banking -- Clinical Presentation and Diagnosis -- Imaging and Staging of Pediatric Liver Tumors -- Pathology of Pediatric Liver Tumors -- Surgical Treatment -- Liver Transplantation for Unresectable Liver Tumors in Children -- Childhood Hepatoblastoma and Hepatocellular Carcinoma -- Salvage Strategies -- Alternative Approaches for Treatment -- Supportive Therapy and Toxicity -- Challenges and Opportunities of International Therapeutic Trials -- Tumors Other than Hepatoblastoma and Hepatocellular Carcinoma -- Future Prospective.
Electronic reproduction.
Keywords: Liver -- Diseases; Pediatric gastroenterology; Tumors in children; Electronic books